Self Disclosure Perempuan Sebagai Orang Tua Tunggal - Alfian Harbiyanto (Jurnal Ilmiah Wahana Pendidikan, 2021)
Marriage is one thing that is a big dream for many individuals. This research is based on a qualitative approach. The word qualitative implies an emphasis on processes and meanings that are not studied rigorously or have not been measured in terms of quantity, intensity, or frequency. Qualitative approach is a process of research and understanding based on a methodology that investigates a social phenomenon and human problem. Every human being must have needs that must be met, including single parents. Human needs are divided into several levels, namely: physiological needs, security needs, needs for love and belonging, esteem needs, and self-actualization needs. These needs must be met in order for life to run smoothly. Basic human needs, namely physiological needs which include: clothing, food, and housing, can certainly be met by single parents even with effort and hard work. The need for security can also be met from the family environment.